Selection criteria of Musa cultivars as determined through a farmer participatory appraisal survey in Uganda - Gold, Cliford S.; Kiggundu, A.; Abera, A.M.K.; Karamura, D. (Cambridge University Press, 2002)
New varieties are often developed on research stations with limited farmer involvement until the final stages of testing. Recently, farmer participatory approaches have been employed to include farmers' input into breeding objectives at much earlier stages of varietal development. This paper reports on a farmer survey in Uganda to record farmer selection criteria for banana cultivars as a pre-breeding activity. From ranked data, bunch size and crop maturation time were the key selection criteria in the county's most important commercial production zones. Stand longevity, taste and crop maturation time were key factors where banana production is in decline and sale of bananas less important. Principal component analysis revealed that, nationally, stand longevity and tolerance of marginal soils were the most important criteria, probably because the larger part of overall production is for subsistence.